A colorimetric and "turn-on" fluorimetric chemosensor for the selective detection of cyanide and its application in food samples. Issue 102 (21st October 2016) - Hu, Jing-Han; Sun, You; Qi, Jing; Pei, Peng-Xiang; Lin, Qi; Zhang, You-Ming
Abstract : A simple cyanide highly selective and sensitive fluorescent enhanced chemosensorHY had been designed and synthesized. Abstract : A novel highly selective isonicotiamide-based chemosensorHY for cyanide was successfully designed and synthesized, which showed both colorimetric and fluorescent turn-on responses for cyanide ions in aqueous. This structurally simple chemosensor could detect CN − anion over other anions in aqueous solution DMSO/H2 O (v/v = 7 : 3) undergo deprotonation reaction. Results showed that the chemosensorHY exhibited 14-fold enhancement in fluorescence at 552 nm and showed yellow fluorescence under the UV-lamp after the addition of CN − in aqueous solution. An obvious change in color from pale yellow to yellow that could be detected by naked eye. We have successfully utilized the above CN − and H + for the fabrication of INHIBIT molecular logic gates, using CN − and H + as chemical inputs and the fluorescence intensity signal as the output. Moreover, the detection limit on fluorescence response of the sensor to CN − is down to 5.12 × 10 −8 M by titration method. Test strips based onHY were obtained, which could be used as a convenient and efficient CN − test kit to detect CN − in aqueous solution. Furthermore, the sensor could detect the CN − in food sample as a sample and effective method.